Adaptation of an Invasive Pest to Novel Environments: Life History Traits of Drosophila suzukii in Coastal and Mainland Areas of Greece during Overwintering - Stella A. Papanastasiou; Vasilis G. Rodovitis; Eleni Verykouki; Evmorfia P. Bataka; Nikos T. Papadopoulos (Biology, 2021)
Drosophila suzukii is a polyphagous pest of small and soft fruit, originating from Asia, which has spread and established in Europe and the USA. Adults exhibit seasonal phenotypes, i.e., summer morphs (SM) and winter morphs (WM) to cope with fluctuating environmental conditions. WM have a darker cuticle and larger wings compared to SM, while WM females experience reproductive dormancy. We studied the life history traits (lifespan, female reproductive status and number of produced offspring) of WM and SM that were exposed to winter field conditions of a coastal and a mainland agricultural area, with mild and cold winter climates, respectively. Mated adults of each phenotype were individually placed in vials bearing nutritional/oviposition substrate, and transferred to the field from November 2019 to May 2020, when the death of the last individual was recorded. Almost all SM females (90%) and no WM female carried mature ovarioles before being transferred to the field. WM exhibited a longer lifespan than SM adjusting for location and sex. Differences in survival between the two phenotypes were more pronounced for adults kept in the mainland area. The majority of SM females produced offspring during overwintering in the mild coastal area, but only a few SM were reproductively active in the cold mainland area. Some WM females produced progeny during overwintering in the mild conditions of the coastal area, but all WM females were in reproductive arrest in the mainland area. Overwintering females in the coastal area had a shorter lifespan and produced more progeny than those kept in the mainland area. High survival rates of WM provide indications of the successful performance of this phenotype in the adverse conditions of the cold climates. Additionally, the continuous reproductive activity of SM females and the onset of progeny production by WM females during overwintering in the coastal area indicate that the insect remains reproductively active throughout the year in areas with mild climatic conditions. Our findings support the successful adaptation of D. suzukii in both areas tested and can be used for the development of area-specific population models, based on the prevailing climatic conditions.